2004
DOI: 10.3758/bf03194912
|View full text |Cite
|
Sign up to set email alerts
|

Object file continuity predicts attentional blink magnitude

Abstract: When asked to identify targets embedded within a rapid consecutive stream of visual stimuli, observers are less able to identify the second target (T2) when it is presented within half a second of the first (T1); this deficit has been termed the attentional blink (AB). Rapid serial visual presentation methodology was used to investigate the relationship between the AB and object files (episodic representations implicated in object identification and perceptual constancy). An inverse linear relationship was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…Suppose that the control condition produced an initially strong but short-lived AB, and the experimental condition produced a longer-lasting AB. Subtracting the latter from the former would produce the performance curve illustrated in Figure 6A of Kellie and Shapiro. That this was indeed the case in Experiment 2 of Kellie and Shapiro (2004) is confirmed by the data in their Figure 6B, which shows separate performance curves for the experimental and the control condition. An asymptotic level of approximately 88% correct identifications of the second target can be estimated by averaging the performance of the control group over the five longest lags, at which performance no longer showed systematic improvement.…”
Section: The Subtraction Procedures Of Estimating the Ab Deficitsupporting
confidence: 71%
See 1 more Smart Citation
“…Suppose that the control condition produced an initially strong but short-lived AB, and the experimental condition produced a longer-lasting AB. Subtracting the latter from the former would produce the performance curve illustrated in Figure 6A of Kellie and Shapiro. That this was indeed the case in Experiment 2 of Kellie and Shapiro (2004) is confirmed by the data in their Figure 6B, which shows separate performance curves for the experimental and the control condition. An asymptotic level of approximately 88% correct identifications of the second target can be estimated by averaging the performance of the control group over the five longest lags, at which performance no longer showed systematic improvement.…”
Section: The Subtraction Procedures Of Estimating the Ab Deficitsupporting
confidence: 71%
“…The subtraction (control minus experimental) procedure can potentially distort the evidence relating to the rate at which the AB develops. A case in point can be found in a study by Kellie and Shapiro (2004), especially in Experiment 2, Figures 6A and 6B. Figure 6A illustrates AB magnitude estimated by the subtraction procedure described above.…”
Section: The Subtraction Procedures Of Estimating the Ab Deficitmentioning
confidence: 94%
“…It is transient, limited to a period of about 200-400 ms after the onset of the first target, and it usually does not affect items appearing within about 100 ms of the first target, so-called lag-1 sparing (Chun & Potter, 1995;Raymond et al, 1992;Potter et al, 1998;Potter, Staub, & O'Connor, 2002). In addition, the cost that selecting a first target incurs to items that appear 100-400 ms later is only seen when the target is followed by a distractor or by a blank interval of more than 100 ms (Nieuwenstein, Potter, & Theeuwes, in press) and not when it is followed by an unbroken sequence of targets (e.g., Di Lollo, Kawahara, Ghorashi, & Enns, 2005;Olivers, 2007;Olivers, Van der Stigchel, & Hulleman, 2007; for related results, see Kellie & Shapiro, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that substantial ABs can be obtained with nonverbal material, such as sym- bols (Ͻ, Ͼ, #,%, ?, /, and *; Chun & Potter, 1995), visual patterns (Kellie & Shapiro, 2004), meaningless visual shapes (Chun & Jiang, 1999;Raymond, 2003), colors (Ross & Jolicoeur, 1999), and time intervals (Sheppard, Duncan, Shapiro, & Hillstrom, 2002). Here we used "letters" from two "Star Trek" alphabets (see Figure 3).…”
Section: Methodsmentioning
confidence: 99%